Phosphoinositide 3-kinase in health and disease Volume 2 - Rommel, Christian; Vanhaesebroeck, Bart; Vogt, Peter K. (Current Topics in Microbiology and Immunology, 2011)
From humble beginnings over 25 years ago as a lipid kinase activity associated with certain oncoproteins, PI3K (phosphoinositide 3-kinase) has been catapulted to the forefront of drug development in cancer, immunity and thrombosis, with the first clinical trials of PI3K pathway inhibitors now in progress. Here the authors give a brief overview of some key discoveries in the PI3K area and their impact, and include thoughts on the current state of the field, and where it could go from here.